A micro-nano composite structure on copper surface and its preparation method and application

By sandblasting the copper surface and ultrasonic reaction to form a micro-nano composite structure, the problem of insufficient heat transfer performance of copper is solved, and the critical heat flow density and heat exchange coefficient are significantly improved, which is suitable for improving the heat dissipation ability of the equipment.

CN115213819BActive Publication Date: 2025-02-11SCNU QINGYUAN INSTITUTE OF SCIENCE & TECHNOLOGY INNOVATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210702169.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-20
Publication Date
2025-02-11
Estimated Expiration
2042-06-20

AI Technical Summary

Technical Problem

The poor heat transfer performance of existing copper materials in heat exchange equipment leads to insufficient heat dissipation capabilities of the equipment and the risk of local temperature being too high.

Method used

The copper surface is sandblasted and a hilly pit is formed, and ultrasonic reaction is carried out in a mixed solution of HCl and H2O2 to form a scaly texture, thereby forming a micro-nano composite structure on the copper surface.

Benefits of technology

It significantly improves the critical heat flow density and heat exchange coefficient of copper materials, improves the heat dissipation ability of the equipment, and the structure is good in stability, suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115213819B_ABST
    Figure CN115213819B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of heat transfer technology, and discloses a copper surface micro-nano composite structure, a preparation method and an application thereof. The copper surface micro-nano composite structure of the present invention comprises a copper substrate and a micro-nano composite structure; the micro-nano composite structure is formed on the surface of the copper substrate, and the micro-nano composite structure comprises hilly pits and scaly textures, and the scaly textures are formed on the surface of the hilly pits. The copper surface micro-nano composite structure of the present invention can significantly improve the critical heat flux density and heat transfer coefficient of the copper material by structurally modifying the copper surface, and the critical heat flux density is as high as 141.4W / cm 2 The maximum heat transfer coefficient is up to 8.7W / (cm 2 ·K); at the same time, since the micro-nano composite structure on the surface of the copper material of the present invention is the result of the combined action of plastic deformation and corrosion, the resulting micro-nano composite structure will firmly exist on the surface of the copper material and has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat transfer technology, and particularly relates to a copper surface micro-nano composite structure and a preparation method and application thereof. Background Art

[0002] With the development of modern science and technology, equipment is becoming increasingly miniaturized, integrated and high-powered, which will lead to an increase in the total heat generated per unit volume in the device, and even the phenomenon of local overtemperature, which is extremely detrimental to the safety and stable operation of the equipment. Therefore, it is very important to improve the heat dissipation capacity of the equipment.

[0003] Copper is widely used in heat exchangers, flat collectors of solar heating devices, pipes and other heat exchange equipment due to its thermal conductivity, electrical conductivity and corrosion resistance. However, the heat transfer performance of copper is not good, and there is still a lot of room for improvement. Structural modification of the copper surface can improve its heat transfer performance, thereby enhancing the heat dissipation capacity of the equipment. Therefore, structural modification of the copper surface has become a research hotspot.

[0004] At present, there are two main types of commonly used structural modifications on the surface of metal materials: the first is to first construct a microstructure on the substrate, and then further deposit or grow a nanostructure on the basis of the microstructure, and finally form a micro-nano composite structure surface. This additive processing method has a certain improvement in heat transfer performance, but the stability is poor. The second is to directly construct a micro-nano composite structure on the substrate, such as focused ion beam etching, photolithography, laser processing, etc. This subtractive processing method has improved stability, but the equipment involved is relatively expensive, and has certain requirements on the properties of the material. The experimental conditions are harsh, and it involves complex and time-consuming processing procedures, and the processing cost is high, all of which limit its practical application. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a copper surface micro-nano composite structure and a preparation method and application thereof. The copper surface micro-nano composite structure of the present invention can significantly improve the critical heat flux density and heat transfer coefficient of the copper material.

[0006] The first aspect of the present invention is to provide a micro-nano composite structure on the surface of a copper material, comprising a copper material substrate and a micro-nano composite structure; the micro-nano composite structure is formed on the surface of the copper material substrate, the micro-nano composite structure comprises hilly pits and flaky textures, and the flaky textures are formed on the surface of the hilly pits.

[0007] Preferably, the size of the hill-like pits is 1-200 μm, and the size of the scaly texture is 20-1000 nm.

[0008] Preferably, the size of the hill-like pits is 50-200 μm, and the size of the flaky texture is 300-1000 nm.

[0009] The second aspect of the present invention is to provide a method for preparing the micro-nano composite structure on the surface of a copper material according to the present invention, comprising the following steps:

[0010] The surface of the copper substrate is sandblasted to obtain the hill-like pits, and then the copper substrate is immersed in a mixed solution of HCl and H2O2 to perform ultrasonic reaction to obtain the scaly texture.

[0011] Preferably, before the sandblasting process, the copper substrate is also pretreated, and the specific process of the pretreatment is:

[0012] The surface of the copper substrate is grinded with 500-2000# sandpaper, and then polished with 6000-15000# polishing board. Finally, the copper substrate is placed in acetone, anhydrous ethanol, hydrochloric acid and water respectively, ultrasonically cleaned for 10-15 minutes, and dried for standby use.

[0013] Preferably, the specific process of the sandblasting is:

[0014] A sand material with a particle size of 12-80 mesh is used, the nozzle is perpendicular to the surface of the copper substrate and 5-8 cm away from the surface of the copper substrate, and the sand blasting time is 10-60 seconds. More preferably, a sand material with a particle size of 12-46 mesh is used.

[0015] Preferably, the concentration of the HCl is 1-3 M, and the concentration of the H2O2 is 0.5-2 wt%.

[0016] Preferably, the ultrasonic reaction time is 10-60 min, the ultrasonic reaction temperature is 25-35° C., and the ultrasonic frequency of the ultrasonic reaction is 10-40 kHz.

[0017] The third aspect of the present invention is to provide an application of the copper material surface micro-nano composite structure of the present invention in heat dissipation and heat transfer equipment.

[0018] Based on the above application, the present invention provides a heat exchanger, comprising the copper material surface micro-nano composite structure described in the present invention.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] The micro-nano composite structure on the surface of the copper material of the present invention can significantly improve the critical heat flux density and heat transfer coefficient of the copper material by structurally modifying the surface of the copper material. The critical heat flux density is as high as 141.4W / cm 2The maximum heat transfer coefficient is up to 8.7W / (cm 2 ·K); at the same time, since the micro-nano composite structure on the surface of the copper material of the present invention is the result of the combined action of plastic deformation and corrosion, the resulting micro-nano composite structure will firmly exist on the surface of the copper material and has good stability.

[0021] The method for preparing the micro-nano composite structure on the surface of a copper material of the present invention has simple process, convenient operation, no need for expensive equipment, low cost, low environmental requirements, and is conducive to realizing its large-scale industrial application in the field of heat transfer. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a 3D topography of the micro-nano composite structure on the surface of the copper material of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the micro-nano composite structure on the surface of the copper material of the present invention;

[0024] Figure 3 It is a scanning electron microscope image of the micro-nano composite structure on the surface of the copper material of the present invention. DETAILED DESCRIPTION

[0025] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0026] Unless otherwise specified, the raw materials or instruments used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0027] Example 1

[0028] A method for preparing a micro-nano composite structure on the surface of a copper material comprises the following steps:

[0029] Step 1: Use the copper plate as the base material, grind it with 500-2000# sandpaper in turn, and then polish the surface with 6000-15000# polishing board until there are no obvious scratches on the surface of the copper plate; then, put the copper plate into acetone, anhydrous ethanol, hydrochloric acid and deionized water in turn, clean it in an ultrasonic cleaner for 15 minutes respectively, and dry it for later use;

[0030] Step 2: The surface of the copper plate is sandblasted, the sand material is aluminum oxide particles, the mesh size is 16 meshes, the sandblasting time is 20 seconds, the sandblasting distance is 6 cm, and 50-150 μm hill-like pits (micrometer-level structure) are formed on the surface of the copper plate; then, the copper plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10 minutes respectively, and dried;

[0031] Step 3: The copper plate with a micron-scale structure obtained in step 2 is immersed in a mixed solution of 2M HCl and 0.5wt% H2O2, and the beaker containing the mixed solution and the copper plate is placed in an ultrasonic cleaning machine for reaction, and a 100-1000nm flaky texture (nanoscale structure) is formed on the surface of the hill-like pits. The time of the ultrasonic cleaning machine is set to 30min, the temperature is 30°C, and the ultrasonic frequency is 30kHz. After taking out, it is dried to obtain a micro-nano composite structure on the surface of the copper material.

[0032] Figure 1 The 3D morphology of the micro-nano composite structure on the surface of the copper material prepared in this example is shown (the coordinate unit in the figure is micrometer, and the structure height values ​​in the figure are 0, 14.533, 29.067, 43.6, 58.134, and 72.667 from bottom to top); Figure 2 , Figure 3 The scanning electron microscope images of the micro-nano composite structure on the surface of the copper material prepared in this example at different magnifications are shown respectively, and it can be clearly seen that hill-like pits and scaly textures formed on the surface of the hill-like pits are successfully obtained on the surface of the copper material.

[0033] Example 2

[0034] A method for preparing a micro-nano composite structure on the surface of a copper material comprises the following steps:

[0035] Step 1: Use the copper plate as the base material, grind it with 500-2000# sandpaper in turn, and then polish the surface with 6000-15000# polishing board until there are no obvious scratches on the surface of the copper plate; then, put the copper plate into acetone, anhydrous ethanol, hydrochloric acid and deionized water in turn, clean it in an ultrasonic cleaner for 15 minutes respectively, and dry it for later use;

[0036] Step 2: The surface of the copper plate is sandblasted, the sand material is aluminum oxide particles, the mesh size is 12 meshes, the sandblasting time is 10s, the sandblasting distance is 5cm, and 50-200μm hill-like pits (micrometer-level structure) are formed on the surface of the copper plate; then, the copper plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10min respectively, and dried;

[0037] Step 3: The copper plate with a micron-scale structure obtained in step 2 is immersed in a mixed solution of 3M HCl and 1.5wt% H2O2, and the beaker containing the mixed solution and the copper plate is placed in an ultrasonic cleaning machine for reaction, and a 300-1000nm flaky texture (nanoscale structure) is formed on the surface of the hill-like pits. The time of the ultrasonic cleaning machine is set to 20min, the temperature is 25°C, and the ultrasonic frequency is 30kHz. After taking out, it is dried to obtain a micro-nano composite structure on the surface of the copper material.

[0038] Example 3

[0039] A method for preparing a micro-nano composite structure on the surface of a copper material comprises the following steps:

[0040] Step 1: Use the copper plate as the base material, grind it with 500-2000# sandpaper in turn, and then polish the surface with 6000-15000# polishing board until there are no obvious scratches on the surface of the copper plate; then, put the copper plate into acetone, anhydrous ethanol, hydrochloric acid and deionized water in turn, clean it in an ultrasonic cleaner for 15 minutes respectively, and dry it for later use;

[0041] Step 2: The surface of the copper plate is sandblasted, the sand material is aluminum oxide particles, the mesh size is 24 meshes, the sandblasting time is 30 seconds, the sandblasting distance is 6 cm, and 20-80 μm hill-like pits (micrometer-level structure) are formed on the surface of the copper plate; then, the copper plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10 minutes respectively, and dried;

[0042] Step 3: The copper plate with a micron-scale structure obtained in step 2 is immersed in a mixed solution of 2M HCl and 0.5wt% H2O2, and the beaker containing the mixed solution and the copper plate is placed in an ultrasonic cleaning machine for reaction, and a 200-800nm ​​flaky texture (nanoscale structure) is formed on the surface of the hill-like pits. The time of the ultrasonic cleaning machine is set to 40min, the temperature is 30°C, and the ultrasonic frequency is 40kHz. After taking out, it is dried to obtain a micro-nano composite structure on the surface of the copper material.

[0043] Example 4

[0044] A method for preparing a micro-nano composite structure on the surface of a copper material comprises the following steps:

[0045] Step 1: Use the copper plate as the base material, grind it with 500-2000# sandpaper in turn, and then polish the surface with 6000-15000# polishing board until there are no obvious scratches on the surface of the copper plate; then, put the copper plate into acetone, anhydrous ethanol, hydrochloric acid and deionized water in turn, clean it in an ultrasonic cleaner for 15 minutes respectively, and dry it for later use;

[0046] Step 2: The surface of the copper plate is sandblasted, the sand material is aluminum oxide particles, the mesh size is 36 meshes, the sandblasting time is 40s, the sandblasting distance is 7cm, and 10-60μm hill-like pits (micrometer-level structure) are formed on the surface of the copper plate; then, the copper plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10min respectively, and dried;

[0047] Step 3: Soak the copper plate with a micron-scale structure obtained in step 2 in a mixed solution of 1M HCl and 1wt% H2O2, and place the beaker containing the mixed solution and the copper plate in an ultrasonic cleaning machine for reaction, forming a 50-600nm flaky texture (nanoscale structure) on the surface of the hill-like pits. The time of the ultrasonic cleaning machine is set to 60min, the temperature is 35°C, and the ultrasonic frequency is 20kHz. After taking out, dry to obtain a micro-nano composite structure on the surface of the copper material.

[0048] Example 5

[0049] A method for preparing a micro-nano composite structure on the surface of a copper material comprises the following steps:

[0050] Step 1: Use the copper plate as the base material, grind it with 500-2000# sandpaper in turn, and then polish the surface with 6000-15000# polishing board until there are no obvious scratches on the surface of the copper plate; then, put the copper plate into acetone, anhydrous ethanol, hydrochloric acid and deionized water in turn, clean it in an ultrasonic cleaner for 15 minutes respectively, and dry it for later use;

[0051] Step 2: The surface of the copper plate is sandblasted, the sand material is aluminum oxide particles, the mesh size is 46 mesh, the sandblasting time is 60s, the sandblasting distance is 8cm, and 1-50μm hill-like pits (micrometer-level structure) are formed on the surface of the copper plate; then, the copper plate is ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 10min respectively, and dried;

[0052] Step 3: The copper plate with a micron-scale structure obtained in step 2 is immersed in a mixed solution of 2M HCl and 2wt% H2O2, and the beaker containing the mixed solution and the copper plate is placed in an ultrasonic cleaning machine for reaction, and a 20-500nm flaky texture (nanoscale structure) is formed on the surface of the hill-like pits. The time of the ultrasonic cleaning machine is set to 60min, the temperature is 25°C, and the ultrasonic frequency is 10kHz. After taking out, it is dried to obtain a micro-nano composite structure on the surface of the copper material.

[0053] Comparative Example 1

[0054] The difference between Comparative Example 1 and Example 2 is that in step 3 of Comparative Example 1, a mixed solution of 3M H2SO4 and 1.5wt% H2O2 is used for immersion, and other preparation conditions are the same as those of Example 2.

[0055] Performance Testing

[0056] Using deionized water as the working fluid, conventional pool boiling heat transfer performance tests were performed on the samples prepared in Examples 1-5, Comparative Example 1, and the control group (ordinary smooth copper plate), respectively, in the following steps:

[0057] Step 1: Determine the temperature measurement point on the main heater and install the corresponding thermocouple, connect the Agilent data acquisition instrument, and the data acquisition system records the thermocouple readings throughout the process;

[0058] Step 2: The entire main heater is embedded in a PTFE-based base and then mounted on the bottom of the stainless steel chamber;

[0059] Step 3: Inject deionized water into the boiling chamber to a depth of 10 cm above the sample surface;

[0060] Step 4: Heat the deionized water to boiling for 40 minutes, and keep the atmospheric pressure in the boiling chamber;

[0061] Step 5: Heat the main heater, and after the thermocouple reading is stable (the value fluctuation is less than 0.2°C within 10 minutes), gradually increase the power until a sharp increase in the thermocouple value is observed, which means that the critical heat flux density is reached;

[0062] Step 6: Turn off the power and stop the experiment;

[0063] Step 7: Record and process the test data, and calculate the test results of boiling heat transfer performance.

[0064] The test results are shown in Table 1.

[0065] Table 1

[0066] sample <![CDATA[Critical heat flux, W / cm 2 > <![CDATA[Maximum heat transfer coefficient, W / (cm 2 ·K)]]> Example 1 141.4 8.7 Example 2 138.1 8.7 Example 3 129.3 7.5 Example 4 125.9 7.1 Example 5 122.7 6.9 Comparative Example 1 120.6 6.7 Control group 105.7 4.9

[0067] It can be seen from the data in Table 1 that the micro-nano composite structure on the surface of the copper material prepared by the present invention significantly improves the critical heat flux density and the heat transfer coefficient. Compared with the ordinary smooth copper plate, the critical heat flux density is increased by 30.7%, and the maximum heat transfer coefficient is increased by 77.6%. Due to the different immersion mixed solution system in Comparative Example 1, the critical heat flux density and the maximum heat transfer coefficient are significantly decreased.

[0068] The preferred embodiments of the present invention are described in detail above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A micro-nano composite structure on the surface of a copper material, characterized in that: It comprises a copper material substrate and a micro-nano composite structure; the micro-nano composite structure is formed on the surface of the copper material substrate, the micro-nano composite structure comprises hilly pits and scaly textures, and the scaly textures are formed on the surface of the hilly pits; The size of the hill-like pits is 50-200 μm, and the size of the scaly texture is 300-1000 nm; The copper material surface micro-nano composite structure is prepared by a preparation method comprising the following steps: The surface of the copper substrate is subjected to sandblasting treatment to obtain the hill-like pits, and then the copper substrate is immersed in a mixed solution of HCl and H2O2 to perform ultrasonic reaction to obtain the scaly texture; Before the sandblasting process is performed, the copper substrate is pretreated. The specific process of the pretreatment is as follows: The surface of the copper substrate is polished with 500-2000# sandpaper, and then the surface of the copper substrate is polished with 6000-15000# polishing board, and finally the copper substrate is placed in acetone, anhydrous ethanol, hydrochloric acid and water respectively, ultrasonically cleaned for 10-15 minutes, and dried for standby use; The specific process of the sandblasting treatment is: using sand with a particle size of 12 mesh, with the nozzle perpendicular to the surface of the copper substrate and 5 cm away from the surface of the copper substrate, and the sandblasting time is 10 s; The concentration of the HCl is 3M, and the concentration of the H2O2 is 1.5wt%; The ultrasonic reaction time is 20 min, the ultrasonic reaction temperature is 25° C., and the ultrasonic frequency of the ultrasonic reaction is 30 kHz.

2. Application of the copper material surface micro-nano composite structure described in claim 1 in heat dissipation and heat transfer equipment.

3. A heat exchanger, characterized in that: It includes the copper material surface micro-nano composite structure as described in claim 1.